2012
DOI: 10.1136/jmedgenet-2011-100454
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral muscular dystrophy: new insights from compound heterozygotes and implication for prenatal genetic counselling

Abstract: Background Facioscapulohumeral muscular dystrophy (FSHD) is considered an autosomal dominant disease with a prevalence of 1 in 20 000. Almost all patients with FSHD carry deletions of integral copies of tandem 3.3 kb repeats (D4Z4) located on chromosome 4q35. However, FSHD families have been reported in which individuals carrying a D4Z4-reduced allele remain asymptomatic. Recently, it has been proposed that the D4Z4-reduced allele is pathogenic only in association with the permissive haplotype, 4APAS. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…In Italy, a frequency of 1.2% was observed for the permissive FSHD allele associated with a D4Z4 contraction in the general population. 45 For FSHD2, 19% of patients showing all three disease criteria were not affected. 23 Another aspect is the known clinical variability even within the families that was already observed by the first describers of the disease, Landouzy and Dejerine in 1886.…”
Section: Discussionmentioning
confidence: 98%
“…In Italy, a frequency of 1.2% was observed for the permissive FSHD allele associated with a D4Z4 contraction in the general population. 45 For FSHD2, 19% of patients showing all three disease criteria were not affected. 23 Another aspect is the known clinical variability even within the families that was already observed by the first describers of the disease, Landouzy and Dejerine in 1886.…”
Section: Discussionmentioning
confidence: 98%
“…The genotype-phenotype correlation conducted more recently on a large scale using a standardized method of evaluation allowed to estimate that 1) 20% of FSHD patients carry full-length D4Z4 alleles, 2) over 25% of relatives carrying D4Z4 reduced alleles do not have FSHD, 3) 3% of healthy subjects from the general population carry D4Z4 reduced alleles 4) no specific 4q haplotype is uniquely associated with FSHD. Remarkably, these studies established as a general rule rather than an exception that detection of a D4Z4 reduced allele is not sufficient to predict FSHD (Scionti et al, 2012a;Scionti et al, 2012b). Over the years, the molecular etiology of FSHD has remained enigmatic, and the literature is filled with claims of causes that fail to be confirmed by other groups.…”
Section: Discussionmentioning
confidence: 99%
“…First a study conducted on 750 unrelated FSHD families from Italy revealed that the frequency of individuals carrying two D4Z4 reduced alleles (compound heterozygotes) is 2,7%, a frequency much higher than expected for a fully penetrant autosomal dominant disorder with prevalence of 1 in 20,000. Interestingly in these families with compound heterozygosity, 25% of relatives carrying D4Z4-reduced alleles and 4A161PAS are healthy (Scionti et al, 2012a). Second, characterization of 253 unrelated FSHD probands from the Italian National Registry for FSHD showed that only 127 of them (50.1%) carry D4Z4 alleles with 1-8 D4Z4 associated with 4A161PAS, whereas the remaining FSHD probands carry different haplotypes or alleles with greater number of D4Z4 repeats (Scionti et al, 2012b).…”
Section: Permissive and Non-permissive Genetic Backgroundmentioning
confidence: 98%
“…While there is no linear relationship, there is an imperfect correlation among the extremes of pathogenic sized arrays, as FSHD1 subjects with 1-3 repeat units tend to be clinically severe cases while subjects with 8-10 repeats often present with milder symptoms or can be asymptomatic (104,127,148,160,170). In addition, the current accepted genetic requirements for FSHD are present in *1-3% of the general population, typical of a common genetic variant and two orders of magnitude higher than the reported incidence of FSHD, highlighting that these genetic conditions are merely disease permissive (128,140).…”
Section: Fshd Genetics and Clinical Presentationmentioning
confidence: 99%